PELAKSANAAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 116/PUU-VII/2009 TERHADAP PENGANGKATAN 11 KURSI PADA DEWAN PERWAKILAN RAKYAT PAPUA SEBAGAI AMANAT DARI PASAL 6 AYAT (2) UNDANG-UNDANG NOMOR 21 TAHUN 2001 TENTANG OTONOMI KHUSUS BAGI PROVINSI PAPUA - , Elsius Fred Aragae, SH; , Aminoto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objectives study of this entitled research âConstitutional Court Judgment Implementation Number 116/PUU-VII/2009 Toward 11 Papua Legislative Assembly Promotion Seat As a Mandate In Article 6 Paragraph (2) Law Number 21 Of 2001 Concerning The Specific Autonomy For Papua Provinceâ are to know the Constitutional Court Judge consideration and how far the local government runs the Constitutional Court Judgment implementation and also to know obstacles which the government finds in following up the Constitutional Court Judgment. This research is a combination between normative law research and empirical law research as a complement to support the law argumentation. Data collection tool used is documentary study and field study. Data obtained then analyzed by using qualitative method to result in conclusion. The research result shows that Constitutional Court Judge sees that there is a specification of Law No. 21 of 2001 which is acknowledged by Indonesian Republic Constitution. Thus, Constitutional Court Judge considers that Article 6 Paragraph (2) in Law No. 21 of 2001 remains valid although the Indonesian election system and Law No. 10 of 2008 concerning the House Of Representative (DPR), Regional Political Assembly (DPD), and Regional House of Representatives (DPRD) Elections beckon by means of Direct Election by the people. Therefore, Constitutional Court Judge considers the Judgment based on historical interpretation and systematical or logical interpretation. In the judgment declares that Papua Legislative Assembly (DPRP) membership referring to the Article 6 Paragraph (2) Law No. 21 of 2001 is by means of promotion method and on behalf of Papua origin by using communal/colleague system. Furthermore management has to be arranged by Specific Regional Regulation (Perdasus) in order that the local government has perceived the Constitutional Court Judgment after arranged the Specific Regional Regulation Program about the Papua Province Legislative Assembly (DPRP) Membership Promotion Period 2009-2014. The Specific Regional Regulation Program has been being in the Papua Province Legislative Assembly (DPRP) decides to become Specific Regional Regulation soon. Local government juridical obstacles in arranging Specific Regional Regulation of the DPRP membership Promotion are the promotion method, the use of communal and colleague system and Specific Regional Regulation validation concerning the DPRP membership promotion period 2009-2014. The running efforts are firstly, form the new Specific Regional Regulation which is more democratic as the Article 6 Paragraph (2) Law No. 21 of 2001 implementation so that Specific Regional Regulation equalize with political and democratic national law which takes place in Indonesia. Secondly, the local government is able to decide the DPRP membership candidates without do grouping but by using the individual candidates through the district system by requirement that the candidates should be from Papuan origin. Thirdly, the local government has an option whether the Specific Regional Regulation of DPRP membership promotion validates for periodic 2009-2014 or validates in 2014 to the further election by considering the caused impact with this Specific Regional Regulation validation.